2017
DOI: 10.1007/s00004-017-0355-7
|View full text |Cite
|
Sign up to set email alerts
|

Classification by Type of the Arches in Gaudí’s Palau Güell

Abstract: Architects and historians commonly claim that when designing the Palau Güell, Gaudí experimented with some architectural elements which would influence his later works, with the arches being prevalent in the building. But, to date, no mathematically thorough study has been conducted in order to determine the type of each of such arches. Furthermore, literature contains subjective and intuitive claims which create ambiguity and contradictions. Owing to the methods used by Gaudí, the arches in Palau Güell are be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…After substituting the boundary conditions X A = 36.325 m, Y B = 31.425 m into the system of equations (8), the following values for the Weber"s curve The selected set of points P on the ground-base contour of the object through the Approximation II (see Fig. 6 -Approximation II), gives the following coefficient of determination II R 2 = 0.9992.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After substituting the boundary conditions X A = 36.325 m, Y B = 31.425 m into the system of equations (8), the following values for the Weber"s curve The selected set of points P on the ground-base contour of the object through the Approximation II (see Fig. 6 -Approximation II), gives the following coefficient of determination II R 2 = 0.9992.…”
Section: Resultsmentioning
confidence: 99%
“…Gonzalez et al determined a curve, which best fits an architectural arch and its analytical equation, and then they apply this method to the 23 arches in Palau Guell, [8]. Authors have concluded that Gaudi experimented with the four types of conic curves (circle, ellipse, parabola, hyperbola) and the two types of hyperbolic-cosine curves (Rankine, catenary).…”
Section: Introductionmentioning
confidence: 99%
“…The second class of investigations underlines the following question: what geometric shape, that is, curve, best fits the contour of particular architectural object either as the whole or one of its components. This problem has been treated by multiple authors including González et al (2018), Samper et al (2017), Petrović et al (2016Petrović et al ( , 2018 and Huylebrouck (2007). In the research of Samper et al (2017), the comparison of the types of conics and hyperbolic-cosine curves in the approximation of Gaudi's geometric forms has been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of such a curve approximation approach can provide a base for further computer modelling for the sake of the preservation of cultural heritage. For example, González et al (2018) determined a curve which best fits an architectural arch and its analytical equation, and then applied this method to the 23 arches in Palau Guell. The authors concluded that Gaudi had experimented with the four types of conic curves (circle, ellipse, parabola and hyperbola) and the two types of hyperbolic-cosine curves (Rankine and catenary).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation